The impact of social responsibility and corporate governance on financial distress - mehamed khatab, noha (Journal of Research in Finance and Accounting, 2023)
This research aims to study the impact of corporate governance and carrying out social responsibility activities in reducing the occurrence of financial default and the exit of the troubled establishment from bankruptcy and thus improving the credit rating of the company. Social reduces the probability of corporate bankruptcy, which enhances sustainability in the long term, as well as companies that obtained excellent scores in the index of social responsibility and governance have higher credit ratings